2020
DOI: 10.1088/1361-6528/abb15f
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the performance of ZnO microrod metal-semiconductor-metal photodetectors via surface capping of thin amorphous Al2O3 shell layer

Abstract: 1D ZnO nanostructures have been widely explored due to their potential applications in ultraviolet (UV) region photodetectors because of their unique structural and optoelectronic properties. However, a large number of surface defect states leading to a noticeable dark current hinders their practical applications in UV photodetection. In this work, we have shown improved ZnO/Al 2 O 3 core-shell microrod photodetectors, whose performance is significantly enhanced by defect passivation and the introduction of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…One possible explanation is the formation of trap states at the surface, which was commonly observed in the ZnO‐based UV PD devices. [ 58,59 ] However, such an opinion is not supported by the time‐resolved photocurrent (Figure 3D) and RT steady‐state PL results (Figure 5B). We anticipate that the sputtered Au NPs have little impact on the surface of CsPbBr 3 due to the very low sputtering power (2 W).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One possible explanation is the formation of trap states at the surface, which was commonly observed in the ZnO‐based UV PD devices. [ 58,59 ] However, such an opinion is not supported by the time‐resolved photocurrent (Figure 3D) and RT steady‐state PL results (Figure 5B). We anticipate that the sputtered Au NPs have little impact on the surface of CsPbBr 3 due to the very low sputtering power (2 W).…”
Section: Discussionmentioning
confidence: 89%
“…If not so, the response speed will be lowered due to the typical charge carriers trapping and de‐trapping process. [ 58,59 ] Meanwhile, as the nonradiative recombination centers, trap states will further deteriorate the RT PL performance. [ 60 ] As a result, it is reasonably suggested that the enhanced photocurrent and photo sensitivity in the Au@CsPbBr 3 PD shown in Figures 3A, B, and C originate from the localized Schottky junction formed at the Au NPs/CsPbBr 3 interface, as shown in Figure 4D.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, strategies for surface modifying will be effective ways to enhance the performance of 1D MW-based PD devices by tuning the charge traps and nonradiative centers. 19 Meanwhile, the core− shell heterojunction can not only take full advantage of different functional materials but also induce novel properties owing to the particular characteristics of the junction. 20 significance in terms of surface modification and the alignment of the energy level configuration.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Alumina (Al 2 O 3 ) is a well-known insulator that possesses good thermal, mechanical, and chemical stability, and it has a relatively high permittivity (ε r ∼ 9.0), high thermal conductivity (∼2–30 W/(m·K)), wide band gap (∼7.0 eV), and high Young’s modulus (∼100 GPa) . These properties make Al 2 O 3 a promising material to enhance the capacitive energy-storage performances of polymer-based dielectrics. ,, Al 2 O 3 has been used as nanofillers to improve the room-temperature performances of PP , and as coating layers to improve the performances of polyimide .…”
Section: Introductionmentioning
confidence: 99%
“…In principle, coating a material with a higher dielectric constant would improve the energy storage more obviously. Alumina (Al 2 O 3 ) is a well-known insulator that possesses good thermal, mechanical, and chemical stability, 26 and it has a relatively high permittivity (ε r ∼ 9.0), 27 high thermal conductivity (∼2−30 W/(m•K)), 28−30 wide band gap (∼7.0 eV), 31 and high Young's modulus (∼100 GPa). 32 These properties make Al 2 O 3 a promising material to enhance the capacitive energy-storage performances of polymer-based dielectrics.…”
Section: Introductionmentioning
confidence: 99%